MicroRNA-34a regulates 5-HT2C expression in dorsal raphe and contributes to the anti-depressant-like effect of fluoxetine. (1st June 2021) - Lo Iacono, Luisa; Ielpo, Donald; Parisi, Chiara; Napoli, Giulia; Accoto, Alessandra; Di Segni, Matteo; Babicola, Lucy; D'Addario, Sebastian Luca; Guzzo, Serafina Manila; Pascucci, Tiziana; Ventura, Rossella; Andolina, Diego
Abstract: Selective serotonin reuptake inhibitors (SSRIs) are designed to improve mood by raising extracellular serotonin levels through the blockade of the serotonin transporter. However, they exhibit a slow onset of action, suggesting the involvement of adaptive regulatory mechanisms. We hypothesized that the microRNA-34 family facilitates the therapeutic activity of SSRIs. We show that genetic deletion of these microRNAs in mice impairs the response to chronic, but not acute, fluoxetine treatment, with a specific effect on behavioral constructs that are related to depression, rather than anxiety. Moreover, using a pharmacological strategy, we found that an increased expression of the serotonin 2C (5-HT2C) receptor in the dorsal raphe region of the brain contributes to this phenotype. The onset of the therapeutic efficacy of SSRIs is paralleled by the desensitization of the 5-HT2C receptor in the dorsal raphe, and 5-HT2C is a putative target of microRNA-34. In this study, acute and chronic fluoxetine treatment differentially alters the expression of 5-HT2C and microRNA-34a in the dorsal raphe. Moreover, by in vitro luciferase assay, we demonstrated the repressive regulatory activity of microRNA-34a against 5-HT2C mRNA. Specific blockade of this interaction through local infusion of a target site blocker was sufficient to prevent the behavioral effects of chronic fluoxetine. Our results demonstrate a new miR-34a-mediated regulatory mechanism of 5-HT2C expression in the dorsal raphe and implicate it in eliciting the behavioral responses to chronic fluoxetine treatment. Graphical abstract: Molecular model of miR-34a/Htr2c regulation in the expression of fluoxetine antidepressant efficacy. In the Dorsal Raphe fluoxetine increases the level of extracellular 5-HT by inhibiting the 5-HT reuptake pump in serotoninergic neurons. The surge of extra-cellular 5-HT activates local gabaergic neurons by stimulating 5-HT2C receptors and up-regulating their transcription. This leads to an inhibition of 5-HT release that counteracts fluoxetine antidepressant activity. Under chronic administration fluoxetine up-regulates miR-34a, which, by targeting htr2c mRNA in gabaergic neurons, down-regulates the synthesis of 5-HT2C receptor. This feedback control on 5-HT2C receptors reduces the fluoxetine-induced gabaergic activation and allows the expression of the antidepressant fluoxetine activity. Image 1 Highlights: Acute and chronic fluoxetine in mice have opposite consequences on RDoC behavioral constructs related to depression. The genetic deletion of miR-34 impairs the response to chronic, but not acute, fluoxetine treatment. Acute fluoxetine upregulates 5-HT2C receptor in the dorsal Raphe, causing a detrimental effect on behavior. Chronic fluoxetine upregulates miR-34a in the dorsal Raphe. Specific blocking of miR34a/5HT2C regulation in vivo prevents the behavioral adaptations to chronic fluoxetine treatment.